Pemetaan Banjir Kawasan Sungai Gadjah Putih dan Evaluasi Kinerja Saluran Drainase RW 14, Sumber, Banjarsari, Surakarta - Handayani, Marita Putri; Fadhilah, Isma Nurul; Al-Farrasi, Mirza Ghulam; Handayani, Kusumaningdyah Nurul (P4W IPB, 2024)
Floods often occur due to river water overflowing to the surface. Flooding can also be caused by land development which increases surface runoff and impacts the drainage system. This can cause a decrease in the performance of the drainage channel. This research aims to map floods caused by runoff from the Gadjah Putih River, and the performance of existing drainage channels in RW 14 Sumber, Banjarsari, Surakarta. The rain data used is rain data from the Pabelan, Mojolaban, and Baki rain stations from 2000 to 2019. The Gumbel method is used to analyze rain return periods, runoff discharge analyzed by using Rational Method. Runoff discharge is explained at return periods of 2, 5, and 10 years, producing discharges of 8.15 m3/s respectively; 9.76 m3/day; and 10.61 m3/day. Floods are mapped using HEC-RAS by conducting steady flow analysis. The results of the flood mapping of the Gadjah Putih River showed that the area that experienced flooding at the return period of 2, 5 and 10 years respectively was 50,326.77 m2; 56,865.37 m2; 60,756.82 m2. Drainage performance analysis compares hydrology and hydraulic calculations. The analysis resulted drainage performance in RW 14 Sumber show that at the 2 year discharge period, 34 types of channels are safe, and 11 types of channels require repair; in the 5 year discharge period, 30 types of channels are safe, and 15 types of channels require repair; at the 10 year discharge period, 25 types of channels are safe, and 20 types of channels require repair.